The Influence of Price Perceptions and Brand Image of Msme Products on Consumer Loyalty - Indah Yuliasari; Karno Karno; Syaiful Syaiful (Journal Research of Social Science, Economics, and Management, 2023)
Creating and retaining customers should be a bigger priority for the company. The right strategy should be prepared carefully so that customers want to buy products or services produced by the company. More than that, with all the tips, the company should also continue to strive so that customers can become loyal customers. In connection with the marketing strategy of MSMEs which is more oriented towards efforts to direct consumers and potential customers to be more loyal to the products or services provided, this study aims to identify and analyze the factors related to consumer loyalty and satisfaction of MSME product users. as the dependent variable, as well as the influence of perceived price and brand image as independent variables. The study uses a quantitative approach. The examining method in this study was to utilize Non-Likelihood Purposive Testing which is an examining strategy that doesn't give equivalent open doors or conceivable outcomes to every component or individual from the populace to be chosen as an example. The example in this study added up to 38 respondents. The information utilizes essential information, in particular utilizing the aftereffects of survey information that has been handled utilizing SPSS 21.00. The results can be concluded that price perceptions have a positive effect on consumer satisfaction and consumer loyalty, and brand image affects the level of consumer loyalty.